## C) 6 và 1/5.(-2/7)+14 và 4/5.(-2/7) D) 7 và 1/6. (-7/6)+10 và 5/6.(-7/6) E) 5/7.5/11+5/7.2/11-5/7.14/11 Ai làm nhanh mk vote 5star.

Question

C) 6 và 1/5.(-2/7)+14 và 4/5.(-2/7)
D) 7 và 1/6. (-7/6)+10 và 5/6.(-7/6)
E) 5/7.5/11+5/7.2/11-5/7.14/11
Ai làm nhanh mk vote 5star.

in progress 0
9 months 2021-04-27T09:55:02+00:00 2 Answers 8 views 0

1. a) 6 1/5 .(-2)/7 + 14 4/5 .(-2/7)
 = (-2)/7 .(6 1/5 + 14 4/5)
 = (-2)/7 .[ (6+14) + (1/5 + 4/5)]
 = (-2)/7 . (20 +1)
 = (-2)/7 . 21
b) 7 1/6 .(-7)/6 + 10 5/6 .(-7)/6
 = (-7)/6 .( 7 1/6 + 10 5/6)
 = (-7)/6 . [(7+10) + (1/6+5/6)]
 = (-7)/6 . (17 + 1)
 = (-7)/6 . 18
c) 5/7 . 5/11 + 5/7 . 2/11- 5/7. 14/11
 = 5/7. (5/11 + 2/11 – 14/11)
 = 5/7 . (-7)/11

f) 19 5/8: 7/12- 15 1/4:7/12
 = 19 5/8 . 12/7 – 15 1/4 . 12/7
 = 12/7 .( 19 5/8 – 15 1/4)
 = 12/7. [(19-15) + (5/8-1/4)]
 = 12/7. (4 + 3/8)
 = 12/7 . 4 3/8

g) 2/5. 1/3- 2/15 : 1/5+ 3/5. 1/3
 = 2/5 . 1/3 – 2/15 . 5 + 3/5 . 1/3
 = 2/5 . 1/3 – 2/3 + 3/5 . 1/3
 =2/5 . 1/3 – 2.1/3 + 3/5 . 1/3
 = 1/3.(2/5 – 2 +3/5)
 =1/3. (-1)

h) 4/9. 19 1/3- 4/9. 39 1/3
 = 4/9.(19 1/3 – 39 1/3)
 = 4/9 . [(19 -39) + (1/3-1/3)]
 = 4/9 . (-20)

2. Giải thích các bước giải:

a) 6 1/5 .(-2)/7 + 14 4/5 .(-2/7)

 = (-2)/7 .(6 1/5 + 14 4/5)

 = (-2)/7 .[ (6+14) + (1/5 + 4/5)]

 = (-2)/7 . (20 +1) = (-2)/7 . 21

$\\$
b) 7 1/6 .(-7)/6 + 10 5/6 .(-7)/6

 = (-7)/6 .( 7 1/6 + 10 5/6)

 = (-7)/6 . [(7+10) + (1/6+5/6)]

 = (-7)/6 . (17 + 1)= (-7)/6 . 18

$\\$

c) 5/7 . 5/11 + 5/7 . 2/11- 5/7. 14/11

 = 5/7. (5/11 + 2/11 – 14/11) = 5/7 . (-7)/11

$\\$

f) 19 5/8: 7/12- 15 1/4:7/12

 = 19 5/8 . 12/7 – 15 1/4 . 12/7

 = ( 19 5/8 – 15 1/4).12/7

 =  [(19-15) + (5/8-1/4)].12/7

 = (4 + 3/8).12/7=  4 3/(8) . 12/7

$\\$

g) 2/5. 1/3- 2/15 : 1/5+ 3/5. 1/3

 = 2/5 . 1/3 – 2/15 . 5 + 3/5 . 1/3

 = 2/5 . 1/3 – 2/3 + 3/5 . 1/3

 =2/5 . 1/3 – 2.1/3 + 3/5 . 1/3

 = 1/3.(2/5 – 2 +3/5) =1/3. (-1)

$\\$

h) 4/9. 19 1/3- 4/9. 39 1/3

 = 4/9.(19 1/3 – 39 1/3)

 = 4/9 . [(19 -39) + (1/3-1/3)] = 4/9 . (-20)